Estimating HLA haplotype frequencies from homozygous individuals – A Technical Report. (27th September 2021) - Seitz, Susanne; Lange, Vinzenz; Norman, Paul J.; Sauter, Jürgen; Schmidt, Alexander H.
Abstract: We estimated HLA haplotype frequencies based on individuals homozygous for 4, 5 or 6 loci. Validation of our approach using a sample of over 3.4 million German individuals was successful. Compared to an expectation‐maximization algorithm, the errors were larger. However, our approach allows the unequivocal detection of rare haplotypes.